Development of active packaging films from semirefined carrageenan integrated with rosemary essential oil and TiO2 nanoparticles - Khadijah Husna, Abd Hamid; Tarchiani, Jayakumar; Sarmeswari, Gunasegaran; Nurul Aini, Mohd Azman (Universiti Kebangsaan Malaysia, 2025)
Active packaging films based on semirefined carrageenan (SRC) were fabricated by integrating rosemary essential oil (REO) with varying concentrations of TiO2 nanoparticles (1, 3, 5, and 7 wt. %) using the solvent casting method. FTIR spectra analysis of the SRC films revealed no significant interactions between the SRC compounds, REO, and TiO2 nanoparticles (TiO2NPs). The SRC film with 1 wt% TiO2NPs exhibited the highest tensile strength (26.5890 MPa), while the incorporation of 0.5 wt% REO in the SRC/TiO2 films enhanced the elongation at break of the SRC films. The presence of TiO2NPs and REO reduced the moisture content and water solubility of the SRC films. The SRC film with 1 wt% TiO2NPs displayed lower opacity values; however, the opacity of the films increased with the concentration of TiO2NPs, indicating their suitability for preventing spoilage in photosensitive foods. The integration of REO in the SRC film showed higher antioxidant activity (22.51%). However, the inclusion of TiO2NPs in the films reduced the antioxidant activity, possibly due to the nanoparticles acting as nanofillers in the film matrix and immobilising the essential oil release to the film surface.